(untitled) (International Journal of Nursing Education, 2021)
Background: COVID-19 pandemic, a global issue, enforced education system to shift with distance learning mode. This study assessed students’ satisfaction with emergency distance learning. Methods: A cross-sectional survey was done among 200 nursing students studying in five nursing campuses of Tribhuvan University. To collect data, questionnaires containing 28 statements measuring students’ satisfaction with online learning on a five-point scale was used. The electronic link of the questionnaire was shared to the participants via their emails, vibers and messengers. Descriptive analysis of data was done using SPSS software. Finding and Conclusion: Distance learning classes were taken through Zoom, Microsoft team, email, viber and messenger. Only 49% students were enjoying online platform applications and >90% of them felt need for training regarding use of technology for distance learning. The learning environment was comfortable for >2/3rd of the students, 74.5% were satisfied with the instructor’s encouragement for active learning and >1/3rd had issues with the instructor’s pace of punctuality. The classes were interrupted due to technological error. The internet charges were expensive and students refused practical classes through distance learning mode.